Faktor Yang Mempengaruhi Kesiapsiagaan Masyarakat Pesisir Pantai Terhadap Kejadian Tsunami Di Kelurahan Tondo Kota Palu - Wendi Muhammad Fadhli (Universitas Muhamadiyah Manado, 2020)
Factors influencing the readiness of coastal communities for tsunami events include knowledge, attitudes, fulfillment of basic needs, preparation for handling victims and disaster management. The results of the interview of researchers on March 8, 2019 with the secretary of Lurah Tondo, from 2013-2018 there had never been a simulation or counseling about the tsunami disaster in the Tondo Village. The purpose of this study is to analyze the factors that influence the preparedness of coastal communities against tsunami in Tondo Kelurahan, Kota Palu h. This type of research is quantitative with an analytical approach using cross sectional design. The population in this study are all coastal communities in Tondo, Palu City, totaling 362 families. The sample was 96 people, with cluster sampling technique. The results of the study of 96 respondents good knowledge as much as 45.8%, sufficient knowledge 28.1% and 26% less knowledge. Pearson chi-square test results p value: 0,000. Good attitude as much as 33.3%, enough attitude 54.2% and lack of attitude 12.5%. Pearson Chi-Square test results p value value: 0.001. Fulfillment of basic needs were fulfilled 55.2% and not fulfilled as much as 44.8%. Chi-Square test results p value value: 0.002. Conclusion there is a relationship of knowledge, attitudes and fulfillment of basic needs with the preparedness of coastal communities against the tsunami in the Village of Tondo, Palu City